Edukasi dan Reevaluasi Penyelesaian Sengketa Non Litigasi - Amaliyah, Amaliyah; Sary, Novytha; Syafiin, Rezky Amalia; Annisa, Arini Nur; Yusriana, Yusriana (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Initially, the horizontal conflict occurred due to a miscomprehension by several Ko’mara villagers concerning a number of legal issues such as land disputes and land boundaries. The conflict escalated out of provocations and riots caused by the people, resulting in physical altercations and murderous intent. This is caused by the lack of public non-litigation legal comprehension. This is why implementing an education focusing on non-litigation legal disputes is important in Ko’mara Village of the North Polongbangkeng District. The education aims to give a proper legal understanding of non-litigation legal disputes with a win-win outcome to both parties to ensure harmony. The method used for this research is discussions and workshops. The result of this research has caused an increase of public comprehension on non-litigation legal disputes by a significant amount of 2,796 and ensuring massive public implementation of problem-solving through non-litigation.